Value Creation in the Information Economy: The Triad of AI, Service, and Human Work - Roth, Angela; Benz, Carina; Wilga, Matthäus; Hottum, Peter; Langes, Barbara; Lewandowski, Tom; Nägele, Rainer; Peters, Christoph; Satzger, Gerhard (Journal of Service Management Research, 2024)
Advancements in artificial intelligence (AI), particularly generative AI (GenAI), have revolutionized the value generation in service<a href="https://unihamburgde-my.sharepoint.com/personal/christian_kurtz_uni-hamburg_de/Documents/DL2030/Phase 4/Ziel 3 - Weiterentwicklung der Schwerpunktthemen/02_Triade_Dienstleistung_KI_Arbeit/SMR Journal Article/Final Submission/Roth et al_Revised Version_Value Creation in the Information Economy.docx#_ftn1" title="">[1] as well as work processes and the work environment. However, the transformative potential of AI in the context of service and work must be guided in a way that ensures its alignment with human-centric values and economic goals. Based on an interactive panel and three workshops of service researchers and practitioners at the annual conference of the German Forum for Service Research (DF)² in September 2023, this paper highlights six fields of action. Spanning corporate strategy, processes, and technology, these six fields of action illustrate how future-oriented service research may harness the opportunities of AI for society and the economy, manage associated risks, and foster societal acceptance. They serve as a framework for discussions and initiatives in service research, raise awareness among companies about necessary changes to remain competitive, and highlight funding needs with high relevance, societal importance, and economic potentia
Keywords: Service Research Priorities; Generative AI; Future of Work; Value Creation